Pengaruh Sikap, Norma Subjektif, Kendali Perilaku Persepsian terhadap Intensi Manajemen Laba dengan Machiavellianism sebagai Variabel Moderas - Oktaviani, Ayu; Novika Rosari; MS, Pusvita Indria; Kasyful Anwar; Yohana Yustika Sari; Aulia Rahmi; Sri Febrianti (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
The purpose of this study was to examine the concept of Machiavellianism in moderating the influence of attitudes, subjective norms, and perceived behavioral control on earnings management intentions. This research uses a quantitative approach and adopts the Theory of Planned Behavior. The sample size for this study consisted of 80 Master's students in Accounting and Management at the Faculty of Economics and Business, ULM, chosen through judgment sampling. Data analysis employed moderation regression analysis. The results indicated that attitudes, subjective norms, and perceived behavioral control did not influence earnings management intentions. Consequently, Machiavellianism was unable to moderate the relationships among these three independent variables. This finding suggests that earnings management intentions are not driven solely by a personality trait seeking self-interest (Machiavellianism). The novelty of this study lies in its exploration of Machiavellianism as a moderating factor in earnings management intentions. Future research should explore other variables that could potentially moderate earnings management intentions, thereby developing a more comprehensive and accurate model to explain the intentions and behaviors related to earnings management